Does audit fees and non-audit fees matters in audit quality? - Yuvaraj, Ganesan; Narayanan, Ranjani; Hasnah, Haron; Pitchay, Anwar Allah (KnE Social Sciences, 2019)
The purpose of this paper is to examine the influence of audit fees and non-audit fees on audit quality of the Public Listed Companies in Malaysia. The research is timely as recently, and many business cases have been exploded after an unqualified audit report issued on the financial statement of the company. The quantitative research approach and secondary data utilized for this study. Further, this study employs a cross−sectional which the data collected from 201 listed company on Bursa Malaysia for the financial year ending in 2017. The results reveal that non-audit fees (NAF) and audit fees (AF) have influenced the audit quality (AQ). The finding of this study conducive to auditing literature by enhancing the knowledge of audit scholars and able to assist policy maker such as the Malaysia Institute of Accountants (MIA) in developing new strategy or policies that can enhance the AQ.